Fish Farming in Buckets (Budikdamber) as an Effort to Provide Self-Sufficient Food and Alternative Income - Mutoharoh Mutoharoh; Naila Najihah; Winarsih Winarsih; Luluk Muhimatul Ifada; Zainal Alim Adiwijaya (Universitas Lambung Mangkurat, 2024)
This program was proposed to overcome food problems, limited land for farming and additional income for the society in urban areas. The aquaponics in the bucket technique is a relevant solution to be implemented nowadays for urban communities faced with the increase in food prices issue on the market, as reported by target partners. Implementing aquaponics also has the potential to be an alternative income as this produces commodities with selling value. The implementation of this program involves PKK RW members in Bangunharjo as potential partners due to their background as housewives with a high need for a variety of food ingredients and a source of additional income for the family. This program was implemented for six months, from April until September 2023, covering the preparation, practice, evaluation, and assessment stages using the Participatory Learning and Action method. The results showed quite satisfactory results, with an average of 2 harvests of plants being carried out by each partner group and a mortality rate of farmed fish of 16% or 45 of 280 catfish fingerlings.